Thermodynamic data of dicloxacillin sodium in six pure solvents and three binary solvents - Li, Xunhui; Huang, Xuechuan; Li, Peizhou; Feng, Jin; Ma, Wenchan; Zhang, Jiamin; Wang, Na; Wang, Ting; Hao, Hongxun (Journal of molecular liquids, 2025)
•Solid-liquid equilibrium solubility data for DIC in different solvent systems were determined.•The experimental solubility data were correlated by a combination of five thermodynamic models.•Interaction forces between pure solvents and DIC molecules were calculated by molecular simulation. Solubility data of active pharmaceutical ingredients are critical in the development of the crystallization processes, and are also one of the important properties that could affect dissolution and absorption of drugs in vivo. Herein, the solubility of dicloxacillin sodium (DIC) in six pure solvents and three binary mixtures of solvents was measured by dynamic method in the temperature range of 288.15–318.15 K, and the experimental data were correlated using five different thermodynamic models. Moreover, the apparent thermodynamic properties were also explored, and the molecular simulation was applied to investigate the reasons for differences in solubility. It was found that the solubility of DIC can be influenced by both temperature and solvent composition, and it increases with increasing temperature, with the highest solubility observed in methanol, which is related to the solute–solvent interactions. The fitting results show strong consistency with the experimental data, reinforcing the robustness of these models. The apparent thermodynamic properties show that the dissolution process of DIC in the studied solvents is endothermic and entropic.